THE EFFECT OF REAR SPROCKET SIZE VARIATION ON POWER AND TORQUE ON YAMAHA VIXION MOTORCYCLES IN 2015 - Yoyo Saputro; Imam Prasetyo; Muhammad Thomi Nadhief (Scientific Journal of Mechanical Engineering Kinematika, 2021)
Motorcycles are equipped with a power transfer system that is able to bridge the engine output (engine power and torque) with the demands of road conditions, the sprocket is the last part of the power transfer system, because the sprocket is the part that transmits the engine power to the rear wheels through the chain. Previous researchers changed the size of the sprocket with a sprocket eye larger or 2 points smaller than the standard sprocket, while in this study replaced the rear sprocket with a large number of eyes and 4 points smaller than the standard sprocket. The purpose of this study was to determine the effect of variations in rear sprocket size on power and torque on the 2015 Vixion motor. This study used the data collection method from the daynote test using a dynamometer. The test results are the effect of variations in sprocket sizes 43T, 39T, and 47T resulting in an increase in power and the most optimal torque on the sprocket size 47T with a maximum power data of 16.1 HP, and torque data obtained with sprocket size 47T produces a maximum torque of 14.42 Nm. due to the large number of sprockets and the shorter distance between the front and rear sprockets.